Contrast-enhanced ultrasound monitoring of perfusion changes in hepatic neuroendocrine metastases after systemic versus selective arterial ¹⁷⁷Lu/⁹⁰Y-DOTATOC and ²¹³Bi-DOTATOC radiopeptide therapy - Giesel, F.L.; Flechsig P.; Kuder T.; Schwartz L.; Wulfert S.; Zechmann C.; Bruchertseifer F.; Haberkorn U.; Kratochwil C. (Experimental Oncology, 2013)
Aim - radiopeptide therapy with beta emitter labeled ¹⁷⁷Lu/⁹⁰Y- DOTA(0)-Phe(1)-Tyr(3)-octreotide (DOTATOC) and more recently also alpha emitting ²¹³Bi-DOTATOC are promising new treatments for neuroendocrine tumors. No early predictors for treatment response have been recognized and tumor-shrinkage after radiation therapy appears slowly. In some solid tumors a decline in tumor perfusion was found predictive of final treatment response but the gold standard multiphase computed tomography (CT) has a high radiation burden. Therefore we evaluated the ability of contrast-enhanced ultrasound (CEUS) to evaluate tumor perfusion as a response criteria. 14 patients with hepatic neuroendocrine tumor (NET) metastases were enrolled in the retrospective study. Eleven patients were treated with beta-emitting ¹⁷⁷Lu/⁹⁰Y-DOTATOC, either intravenous (i.v.) (n = 5) or intra-arterial (i.a.) (n = 6) and three patients received alpha-emitting ²¹³Bi-DOTATOC (i.a.). CEUS and contrast-enhanced CT (CE-CT) were performed before and 3 months after treatment. CE-CT and CEUS presented comparable results in the baseline study and in the assessment of perfusion changes due to the different treatment regimes. A therapy related decrease in tumor perfusion is an early predictor of longterm morphologic response. Conclusion: CEUS is available and radiation free technique which showed comparable results for perfusion and diameter of liver metastases compared to CE-CT. Intensity reduction in an arterial phase CEUS can be seen as a positive sign indicating long term tumor response to treatment. Therefore CEUS may be considered as an imaging modality for monitoring early treatment after focal alpha and beta targeted therapy. Key Words: contrast-enhanced ultrasound, radionuclide therapy, treatment response, DOTATOC PET/CT.